The effect of different sources of mesenchymal stem cells on microglia states - Xin, Qiang; Zhu, Wenhao; He, Chuan; Liu, Tianyi; Wang, Haifeng (Frontiers in Aging Neuroscience, 2023)
Microglial reaction plays a key role in the prognosis of traumatic CNS injuries (TBI and SCI). A growing number of studies have shown that mesenchymal stem cells (MSCs) play an important role in regulating microglial states. This review summarizes the effects and mechanisms of different sources of MSCs on microglial states in the last five years. In general, bone marrow-derived mesenchymal stem cells are the most accessible and widely used, and can produce immunosuppressive effects on a variety of brain injuries including TBI through tissue engineering in situ implantation; MSCs mainly regulate inflammatory pathways and promote the states of microglia in the anti-inflammatory direction, which also secrete certain cytokines or extracellular vesicles to affect apoptotic pathways, such as the extracellular vesicles miR-21-5p, acting as a neuronal protector.